Supply Chain Performance of the Cement Packing Plant Using the Supply Chain Operations Reference - Arif Rohman Eko Prasetyo ; Rienna Oktarina; Fitri Hidayanto; Anthony Ferry; Randy Manggala (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This research was conducted to analyze the supply chain using packing plants. This study uses the Supply Chain Operations Reference (SCOR) and Analytical Hierarchy Process (AHP) to determine supply chain performance. There are three SCOR levels which are the determining factors in this study. The result of calculating the score of 23 factors which are the Metrics in Cement Packing Plant. The problem in the supply chain at the packing plant is 10 metrics, with an average performance indicator of 4 metrics, marginal of 5 metrics and poor of 1 metric. There are 8 strategy maps to improve Metrics with a score below 70, with the hope of improving the performance of supply chain as a whole. Keywords: Supply Chain Management, Analytical Hierarchy Process, Supply Chain Operation Reference